TEACHERS’ DIFFICULTIES IN TEACHING WRITING DESCRIPTIVE TEXT AT SENIOR HIGH SCHOOL - Irma Wahyuni; Ulfatun Al Muzaqiah (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
The objectives of this research are to know the difficulties faced by English teachers in teaching writing descriptive text and to know what strategies are used by English teachers to teach writing descriptive text using the blended learning method. This research method is a qualitative descriptive method. The population of this research is English teachers in Senior High School 1 Cigudeg. The sample consisted of 3 English teachers in 10th grade at Senior High School 1 Cigudeg. The writer conducted this research in terms of the teaching difficulties in teaching writing the descriptive text of English teachers at Senior High School 1 Cigudeg. The data in this research was collected using observation, field notes, and interviews. In teaching writing descriptive text, the teachers faced seven difficulties. Those difficulties were related to the teachers, students, and writing itself. It was also found that the teachers used strategies to overcome those difficulties.